2015
DOI: 10.5021/ad.2015.27.3.310
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Metastatic Undifferentiated Pleomorphic Sarcoma from a Mediastinal Sarcoma

Abstract: Undifferentiated pleomorphic sarcoma, known as malignant fibrous histiocytoma, is a malignant neoplasm that arises in both soft tissue and bones. In 2002, the World Health Organization declassified malignant fibrous histocytoma as a formal diagnostic entity and renamed it 'undifferentiated pleomorphic sarcoma not otherwise specified.' It most commonly occurs in the lower extremities and rarely metastasizes cutaneously. We report a case of cutaneous metastatic undifferentiated pleomorphic sarcoma of the buttock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(37 reference statements)
0
5
1
Order By: Relevance
“…6 The appearance of cutaneous metastases from undifferentiated pleomorphic sarcoma has been described in the literature as an ulcerated or skincolored nodule with associated swelling. [7][8][9][10]12 Although we could not find cases simulating a pyogenic granuloma-type tumor, Gounder et al reported a primary case in the palpebral conjunctiva that actually resembled one. 13 An exceptional metastatic undifferentiated pleomorphic sarcoma with giant cells to the acral skin is presented,…”
Section: Sircontrasting
confidence: 52%
See 1 more Smart Citation
“…6 The appearance of cutaneous metastases from undifferentiated pleomorphic sarcoma has been described in the literature as an ulcerated or skincolored nodule with associated swelling. [7][8][9][10]12 Although we could not find cases simulating a pyogenic granuloma-type tumor, Gounder et al reported a primary case in the palpebral conjunctiva that actually resembled one. 13 An exceptional metastatic undifferentiated pleomorphic sarcoma with giant cells to the acral skin is presented,…”
Section: Sircontrasting
confidence: 52%
“…6 Cutaneous metastases in relation with sarcomas are rare (0.26% of all sarcoma cases), leiomyosarcoma being the commonest comprising 43% of all sarcomas with cutaneous metastases, while those caused by undifferentiated pleomorphic sarcoma constituted up to 6% of them, with only seventeen cases reported in English literature to our knowledge, where only two were located on the toes. [7][8][9][10][11][12] Cases of angiomatous form that simulate pyogenic granuloma have been described in relation to cutaneous metastases of renal, hepatic and thyroid carcinomas. 5 Acral cutaneous metastases tend to present as an erythematous and intensely painful swollen finger.…”
Section: Sirmentioning
confidence: 99%
“…Other common sites for distant metastasis include bone (8%), liver (1%), cutaneous tissue (0.6%-1.5%), and brain (1.5%). 4 Patients with brain metastasis usually remain asymptomatic or present as intracranial hemorrhages. 5 However, the presentation of sarcoma as an embolic stroke as illustrated in our case is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Undifferentiated pleomorphic sarcomas have high incidence of local recurrence and metastasis. [1] Accounting for <5% of adult soft-tissue sarcomas, [2] these neoplasms have also been reported in children. [3] Individuals in the age group of 50-70 years are mostly affected with common site being the lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Individuals in the age group of 50-70 years are mostly affected with common site being the lower extremities. [4] However, there have been reports of other rare sites involved by these neoplasms such as retroperitoneum [4] male breast, [5] mediastinum, [1] cutaneous, [6] and pelvic region. [7] CONCLUSION These undifferentiated sarcomas are tumors which do not show distinct line of differentiation and obvious morphological features on histopathology.…”
Section: Discussionmentioning
confidence: 99%